Low-cost alternative flood modeling using CHIRPS data in the Way Garuntang Catchment, Bandar Lampung, Indonesia - Sahid, Sahid; Nana, Yanto Putri; Fahmi, Aziz; M Gilang, Mardika Indra; Ferial, Asferizal; Syukry, Zein Akbar; Wiedad, Diyaulhaq; Devi, Yunida (Universitas Gadjah Mada, 2024)
Floods are hydro-meteorological events that could impact economic losses and threaten human life. Floods are events where water overflows in potential areas due to exceeding the river's capacity. Flood modeling is the key in reducing the impact of losses resulting from flood disasters. Satellite-based rainfall data provides data with spatial and temporal distribution that has the potential to be an alternative as input in flood modeling. The availability of satellite rainfall data as input for flood modeling certainly requires an assessment of the modeling results' accuracy level. This research aims to investigate the performance of flood inundation modeling using CHIRPS data. The accuracy value of flood modeling results is calculated by comparing flood modeling results through Snyder-Alexejev synthetic unit hydrograph discharge calculations, which are then applied to 2D flood hydraulic modeling using HEC-RAS. The findings indicate that as an alternative to rainfall station data to model flood inundation, Chirps data have a level of accuracy that can be considered. Even though there are differences in the extent and depth of flood inundation between CHIRPS data and observation rainfall stations data, the results of modeling with CHIRPS data can contribute to mapping potential flood-prone areas.